Effects of different sports on bone density and muscle mass in highly trained athletes - Andreoli, A.; Monteleone, M.; van Loan, M.; Promenzio, L.; Tarantino, U.; de Lorenzo, A. (Medicine & Science in Sports & Exercise, 2001)
Purpose: It is known that participating in sports can have a beneficial effect on bone mass. However, it is not well established which sport is more beneficial for increased bone mineral density (BMD) and appendicular muscle mass (AMM). This study investigated the effects of different high-intensity activities on BMD and AMM in highly trained athletes. Materials and Methods: Sixty-two male subjects aged 18-25 yr participated in the study. The sample included judo (J; N = 21), karate (K; N = 14), and water polo (W; N = 24) athletes who all competed at national and international level. Twelve age-matched nonathletic individuals served as the control group (C). All athletes exercised regularly for at least 3 h.d-1, 6 d.wk-1. Segmental, total BMD, and AMM were measured with a dual-energy x-ray (DXA) absorptiometry (Lunar Corp., Madison, WI). DXA analysis also includes bone mineral content (BMC) and fat and lean masses. Results: Total BMDC was significantly lower (mean +/- SD: 1.27 +/- 0.06 g.cm-2, P < 0.05) than either judo or karate athletes (total BMDJ (1.4 +/- 0.06 g.cm-2) and total BMDK (1.36 +/- 0.08 g.cm-2)) but not different from the W athletes (total BMDW (1.31 +/- 0.09 g.cm-2)). AMM was significantly lower in the C group compared with the three athletic groups (P < 0.05). Fat mass was higher in the W versus J and K athletes but not different from the C group (P < 0.05). Conclusions: This cross-sectional study has shown that athletes, especially those engaged in high-impact sports, have significantly higher total BMD and AMM than controls. These results suggest that the type of sport activity may be an important factor in achieving a high peak bone mass and reducing osteoporosis risk.